Urethral Diverticula in an Australian Cattle Dog Puppy: Clinical Treatment Based on Radiographic and Ultrasonographic Findings - Pires Suppi, Andriele; Castro Lopes Evangelista, Gabriela; Kniphoff da Cruz, Igor Cezar; Garcia, Fredderico; Pulz Doiche, Danuta; Rossi Feliciano, Marcus Antônio (Acta Scientiae Veterinariae, 2025)
Background: Urethral diverticulum is rare in animals, presenting with variable clinical signs, such as urinary incontinence and dysuria. It is typically of congenital origin and can be classified, according to location, in prostatic, membranous, and penile, as well as by form, in saccular and diffuse. Reports in the veterinary literature are limited mainly to isolated cases in dogs, a single cat, and 1 horse. This case report aims to describe the radiographic and ultrasonographic findings, as well as the clinical response to treatment, in the youngest dog diagnosed with this anomaly. Case: A 57-day-old male Australian Cattle Dog presented with a history of dysuria, oliguria, and urinary incontinence. Physical examination revealed no abnormalities. Mild changes were observed in hematological, biochemical, and urinalysis profiles. The result of the hemoparasite screening was negative. Plain abdominal radiographs suggested hepatomegaly and nephromegaly, but were inconclusive for visualization of the urinary tract. Abdominal ultrasonography revealed saccular dilations in the prostatic urethra, bilateral ureteral dilation, mild bilateral pyelectasia, and urinary sedimentation in the bladder. A retrograde urethrocystography confirmed multiple saccular dilations in the membranous and prostatic urethra. Based on these findings, a diagnosis of urethral diverticula was established, and a medical management approach was initiated, including antibiotics, gastroprotectants, and manual bladder compression. After 30 days, the patient showed significant clinical improvement, with normalization of urination and reduced urinary incontinence, which remained only during periods of agitation. Follow-up physical and laboratory examinations were unremarkable. However, the patient was not returned for continued monitoring, precluding long-term evaluation of therapeutic outcome. Discussion: To date, urethral diverticulum involving both portions of the urethra has been reported in only 1 other dog, among several others with an average age of 11 months at diagnosis. The dog in this report did not exhibit any physical examination abnormalities that could reinforce this suspicion, except for urinary incontinence and dysuria, which were associated with slow emptying of the diverticula and with urethral compression, respectively. The mild bilateral pyelectasis and bilateral ureteral dilation in this report can be considered secondary findings resulting from urinary flow overload, while urinary sedimentation may be associated with increased urine concentration and delayed bladder emptying. Physical examination and even rectal palpation may not be useful in identifying urethral diverticula; therefore, a combination of conventional imaging techniques was employed, given that imaging modalities such as magnetic resonance imaging and micturating cystourethrography, though effective in humans, are difficult to apply in routine veterinary practice. A clinically based medical treatment approach was chosen, since surgical correction may not fully resolve urinary incontinence and could lead to complications. The placement of an artificial urethral sphincter, although a less invasive therapeutic option, may worsen the condition in the long term. The patient showed significant clinical improvement after 30 days. This case represents the 1st documented occurrence of multiple diverticula in such a young dog, successfully diagnosed through contrast radiography and ultrasonographic findings that had not previously been described in veterinary literature. Given the absence of the patient from the hospital after the final assessment, it was not possible to monitor the case until complete resolution or to propose a new therapeutic intervention. Keywords: urinary incontinence, dysuria, retrograde urethrocystography.